Piano Sonatas. Paris: Henry Lemoine, vol. 2 - Beethoven, Ludwig van, 1770-1827:::Creator::: (2025)
Volume 2 of five volumes containing the 38 piano sonatas and sonatinas published in a miniature score format by Lemoine.